2016
DOI: 10.1007/s10753-016-0409-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dexamethasone and L-NAME on Acute Lung Injury in Rats with Lung Contusion

Abstract: The therapeutic efficiency of an anti-inflammatory agent, dexamethasone (DXM), and a nitric oxide synthase (NOS) inhibitor, Nitro-L-arginine methyl ester (L-NAME), in lung tissue injury after lung contusion was investigated. Serum levels of tumor necrosis factor-alpha (TNF-α), interleukin-10 (IL-10), YKL-40, an inflammatory peptide, inducible NOS (iNOS), and Clara cell protein 16 (CC-16) were evaluated. Immunohistochemical analyses were also performed, and the lung tissue was examined histopathologically. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In the present study, CLP-induced rats, a well-established sepsis model [ 13 ] and LPS-induced HK-2 cells were used to explore the effects of EsA on septic AKI. DXM is usually used for treatment of inflammatory diseases and exhibits protective effects against sepsis in animal models [ 4 , 5 , 16 ]. Here, the effects of EsA were compared with those of DXM.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, CLP-induced rats, a well-established sepsis model [ 13 ] and LPS-induced HK-2 cells were used to explore the effects of EsA on septic AKI. DXM is usually used for treatment of inflammatory diseases and exhibits protective effects against sepsis in animal models [ 4 , 5 , 16 ]. Here, the effects of EsA were compared with those of DXM.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10, a potent immunomodulatory and anti-inflammatory cytokine (Couper et al, 2008) is included in this action. Kozan et al (2016) confirmed that DEXA regulated acute lung injury through an increase in IL-10 secretion. IL-10 is included in negative regulation of corticosterone synthesis in the adrenal gland (Koldzic-Zivanovic et al, 2006), suggesting a homeostatic mechanism to end hypothalamic-pituitaryadrenal (HPA) axis activation after resolving inflammation.…”
Section: Discussionmentioning
confidence: 54%
“…Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is characterized by clinically significant hypoxemia, diffuse bilateral pulmonary infiltration, pulmonary oedema, a decrease in pulmonary compliance, and a decrease in the functional residual capacity and develops through excessive and uncontrolled systemic inflammatory responses to direct or indirect lung injury . The clinical disorders that are most commonly associated with the development of ALI are pneumonia, sepsis, pulmonary contusion, major trauma, and ischaemia–reperfusion injury . There is good scientific understanding of the epidemiology and pathogenesis of ALI, but the condition remains a significant source of critically ill patients.…”
Section: Discussionmentioning
confidence: 99%